Progressus as an Explanatory Model: An Anthropological Principle Illustrated by the Russia-Ukraine War - Ertl, Paul (Conatus - Journal of Philosophy, 2023)
At the beginning of the Russian Federation’s attack on Ukraine in February 2022, the European Union put up massive resistance, but due to its sudden overload, it was unable to deal with the situation adequately. It was in a state of paralysis for some time. Therefore, five explanatory models for the Russian actions are presented: an offensive, a defensive, a situational, a socio-cultural, and an ideological-historical one. It is then shown that the German term Gewalt, which combines the English terms violence, power, and force ontologically, is best suited to summarize and describe all these models. It is also shown that Gewalt is a neutral, fundamental human concept that can be described as one of the basic driving forces of man. By piercing society, Gewalt constitutes an impulse, a motivation that stimulates and fuels the individual and society in toto. This leads to what we call Progressus, which depends on four variables – group desire, potential means of violence and force, group aims and objectives, as well as group comparison and evaluation. Progressus is inherent in all persons and in all societies. It can be analyzed and managed in a variety of different ways. Combined with the foundation of Gewalt, seen as neutral agent in varying levels of intensity, Progressus forms a matrix for efficient analysis to describe positive and frictional interaction, establishes social relations from friendship up to war; and this between individuals, groups and/or states. How this is possibly implemented in practice is described at the end using an example from the previously presented explanatory models.